Hubungan Pengetahuan Terhadap Perilaku Masyarakat Dalam Pemberantasan Sarang Nyamuk Aedes Aegypti Di Wilayah Kerja Puskesmas Pal. 3 Pontianak - Salbiah Kastari; Susilawati Susilawati; Iswono Iswono (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Dengue Hemorrhagic Fever (DHF) is transmitted through the bite of the Aedes aegypti mosquito and possibly the Aedes albopictus mosquito. The incidence of DHF in Indonesia in the last 3 years of 2018 was 65,602 cases, in 2019 as many as 138,127 cases, and in 2020 as many as 108,303 cases. In West Kalimantan, in 2018, as many as 3,125 cases, in 2019 as many as 2,798 cases, and in 2020 as many as 784 cases. Meanwhile, data on dengue cases in Pontianak City, in 2018 there were as many as 182 cases, in 2019 there were as many as 106 cases, and in 2020 there were as many as 27 cases. Nationally, cases of DHF fluctuate, while in West Kalimantan to Pontianak, it tends to decrease. The death rate (CFR) due to DHF cases in Pontianak City during the period 2018-2019 showed the highest mortality rate occurred in 2018 with a percentage of 1,54% of 100 DHF cases. However, the incidence rate is still there, and every year (endemic) and always has the potential to cause outbreaks. Therefore, efforts to control mosquitoes carrying dengue disease are needed, starting by assessing community knowledge and behavior in controlling DHF disease with nest eradication. Mosquitoes (PSN 3M plus). Objective To examine the relationship between knowledge and community behavior in PSN 3M plus in the work area of ​​the Pal.3 Pontianak Health Center. Methodology is observational research with a cross-sectional approach. The results of the study showed that there was a significant relationship between knowledge and PSN 3M plus in the work area of ​​the Pontianak Pal.3 Health Center, with a value of p = 0.000 (p<). Most respondents have poor knowledge in PSN 3M plus (61,7%), as well as bad behavior in PSN 3M plus (77,7%), so it is concluded that there is a significant relationship between respondents' knowledge and behavior in PSN 3M Plus in the work area of ​​the Pontianak Pal. 3 Health Center.